Monocyte-endothelial cell interactions in vascular and tissue remodeling - Medrano-Bosch, Mireia; Simón-Codina, Blanca; Jiménez, Wladimiro; Edelman, Elazer R.; Melgar-Lesmes, Pedro (Frontiers in Immunology, 2023)
Monocytes are circulating leukocytes of innate immunity derived from the bone marrow that interact with endothelial cells under physiological or pathophysiological conditions to orchestrate inflammation, angiogenesis, or tissue remodeling. Monocytes are attracted by chemokines and specific receptors to precise areas in vessels or tissues and transdifferentiate into macrophages with tissue damage or infection. Adherent monocytes and infiltrated monocyte-derived macrophages locally release a myriad of cytokines, vasoactive agents, matrix metalloproteinases, and growth factors to induce vascular and tissue remodeling or for propagation of inflammatory responses. Infiltrated macrophages cooperate with tissue-resident macrophages during all the phases of tissue injury, repair, and regeneration. Substances released by infiltrated and resident macrophages serve not only to coordinate vessel and tissue growth but cellular interactions as well by attracting more circulating monocytes (e.g. MCP-1) and stimulating nearby endothelial cells (e.g. TNF-α) to expose monocyte adhesion molecules. Prolonged tissue accumulation and activation of infiltrated monocytes may result in alterations in extracellular matrix turnover, tissue functions, and vascular leakage. In this review, we highlight the link between interactions of infiltrating monocytes and endothelial cells to regulate vascular and tissue remodeling with a special focus on how these interactions contribute to pathophysiological conditions such as cardiovascular and chronic liver diseases.